Analisis Kinerja Pegawai Badan Kesatuan Bangsa dan Politik Kabupaten Malinau - Lalong, Etha Margharetha; Darmanto; Sidi, Pramono (Jayapangus Press, 2023)
The human resource factor as an implementing element really needs attention, because employees are the main element of the state apparatus which carries out government tasks in order to achieve national goals. However, it is still found that the performance of government agencies needs improvement, such as the Malinau Regency National Unity and Political Agency. This research will analyze seven employee performance indicators and the efforts that have been made to improve employee performance. This research uses a descriptive qualitative approach, with data collection techniques based on the results of interviews, observations and documentation as primary data. Furthermore, secondary data comes from scientific journals accessed online and books related to employee performance management. The data obtained was studied based on employee performance management theory which is based on seven performance indicators. The research results found that the performance analysis was as follows: (1) the elements have attempted to realize governance that is oriented towards public services; (2) elements of employee targets by understanding and implementing basic tasks and functions; (3) standard elements with employee performance targets; and (4) and the element of feedback through staff review instruments. These four elements have been implemented well. As for other elements; (5) tools/facilities are not yet adequate due to limited means of transportation; (6) the competency element is still dominated by employees with elementary-high school graduates as much as 55%; and (7) the element of employee motive because they are comfortable with the status of a civil servant, and opportunities for advancement in their career path are still minimal. It can be said that this has not been implemented well. This has an impact on the lack of performance innovation and employee career paths which are still static. Efforts have been made to increase employee competency through study permits for higher education, technical guidance, training, preparation of coordination meeting schedules, assessments in each regional organization as well as exemplary employees, and cooperation between agencies.